AVLONI’S VIEWS ON EDUCATION AND UPBRINGING: FOUNDATIONS OF ENLIGHTENMENT - Xolova Mohikul Shavkatovna; Khudoykulov Sunnat Ismattillo oglu (European Science Publishing, 2025)
This article analyzes Abdulla Avloni’s views on education and upbringing as the foundation of enlightenment. The author studies Avloni’s pedagogical ideas, his role in the development of national education, and the importance of his works for modern society. Avloni believed that upbringing forms both the mind and morality of a person. His ideas about ethics, knowledge, and patriotism remain relevant in the 21st century. The article explains Avloni’s educational philosophy and its influence on contemporary educational reforms.
Keywords: Abdulla Avloni, education, upbringing, pedagogy, morality, enlightenment, modernity, society.